Search for new particles in two-jet final states in 7 TeV proton-proton collisions with the ATLAS detector at the LHC - Anduaga, Xabier Sebastián (2010)
A search for new heavy particles manifested as resonances in two-jet final states is presented. The data were produced in 7 TeV proton-proton collisions by the LHC and correspond to an integrated luminosity of 315nb-1 collected by the ATLAS detector. No resonances were observed. Upper limits were set on the product of cross section and signal acceptance for excited-quark (q*) production as a function of q* mass. These exclude at the 95% C.L. the q* mass interval 0.30<mq*<1.26TeV, extending the reach of previous experiments. © 2010 CERN, for the ATLAS Collaboration.